Simultaneous assessment of nitrosamines NDBA, NDEA, NDMA, and NDIPA: quantitative and qualitative analysis using FTMIR KBr pellets and ATR-FTMIR spectroscopy - Martini, Paulo Roberto Rodrigues; Elton Luis Gasparotto Denardin; Clésio Soldateli Paim; Andreas Sebastian Loureiro Mendez (Drug Analytical Research, 2026)
Since nitrosamines (NAs) were first detected in pharmaceutical products in July 2018, new quality assurance and quality control (QA/QC) strategies have emerged. However, few studies have explored the use of conventional FTMIR or ATR-FTMIR spectroscopy for quantifying these impurities. This study evaluated and compared the analytical performance of both ATR-FTMIR and FTMIR KBr-pellet methods for the quantification of four nitrosamines: NDMA, NDEA, NDIPA, and NDBA. Limits of detection (LOD) and quantification (LOQ) were determined for each compound using both techniques. Initially, NDEA was analyzed in methanol solution; subsequently, all four nitrosamines were assessed in potassium bromide (KBr) matrices using both methodologies simultaneously. For NDEA in methanol, the ATR-FTMIR method yielded an LOD of 2.77 × 10⁻³% (v/v) and an LOQ of 9.22 × 10⁻³% (v/v). For NDMA analyzed by ATR-FTMIR with KBr, the LOD and LOQ were approximately 4.94 × 10⁻⁴% and 1.65 × 10⁻³%, respectively. The best sensitivity was achieved for NDBA using the FTMIR KBr-pellet method, which gave the lowest overall values: an LOD of 5.52 × 10⁻⁶% and an LOQ of 1.83 × 10⁻⁵%. The four nitrosamines exhibited distinct physicochemical properties that influenced their spectral responses and, consequently, their analytical performance under the tested conditions. When comparing the two techniques, only the FTMIR KBr-pellet method yielded LODs within regulatory limits for the qualitative detection of NDBA and NDIPA, indicating its superior sensitivity for these compounds.